TINJAUAN STABILITAS KEUANGAN BANK MELALUI TINGKAT PERSAINGAN DAN DIVERSIFIKASI PENDAPATAN: STUDI PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nova, Nova (JURNAL FAIRNESS, 2015)
This study investigated the relationship between the level of competition between banks and revenue diversification on financial stability of commercial banks during 2008- 2013. The level of competition in this study measured by the market share of net interest income. Revenue diversification measured using Hirscman Herfindhal Index, while the bank's financial stability is measured by ZScore for banking industry. Models were analyzed using a fixed effect regression models. The results showed that the bank samples is vurnerable to the intense of competition. Although the research sample has relatively high market share, but its has not shown the resilience to face the competition. Low level of revenue diversification on bank samples showed that they did not implement a diversification strategy, then can not gain benefit from revenue diversification strategy